A pain in the ACC - Frankland Paul W; Teixeira Cátia M (SAGE Publishing, 2005)
Abstract An emerging theme in systems neurobiology is that even simple forms of memory depend on activity in a broad network of cortical and subcortical brain regions. One key challenge is to understand how different components of these complex networks contribute to memory. In a new study in Molecular Pain, Tang and colleagues use a novel set of approaches to characterize the role of the anterior cingulate cortex (ACC) in the formation of Pavlovian fear memories.